Foliar Aphid Herbivory Alters the Tomato Rhizosphere Microbiome, but Initial Soil Community Determines the Legacy Effects - French, Elizabeth; Kaplan, Ian; Enders, Laramy (Frontiers in Sustainable Food Systems, 2021)
Aboveground herbivory can impact the root-associated microbiome, while simultaneously different soil microbial communities influence herbivore performance. It is currently unclear how these reciprocal top-down and bottom-up interactions between plants, insects and microbes vary across different soils and over successive plant generations. In this study, we examined top-down impacts of above-ground herbivory on the rhizosphere microbiome across different soils, assessed bottom-up impacts of soil microbial community variation on herbivore performance, and evaluated their respective contributions to soil legacy effects on herbivore performance. We used Macrosiphum euphorbiae (potato aphid) and Solanum pimpinellifolium (wild tomato) to capture pre- domestication microbiome interactions with a specialist pest. First, using 16S rRNA sequencing we compared bacterial communities associated with rhizospheres of aphid- infested and uninfested control plants grown in three different soils over three time points. High aphid infestation impacted rhizosphere bacterial diversity in a soil- dependent manner, ranging from a 22% decrease to a 21% increase relative to uninfested plants and explained 6-7% of community composition differences in two of three soils. We next investigated bottom-up and soil legacy effects of aphid herbivory by growing wild tomatoes in each of the three soils and a sterilized “no microbiome” soil, infesting with aphids (phase one), then planting a second generation (phase two) of plants in the soil conditioned with aphid-infested or uninfested control plants. In the first phase, aphid performance varied across plants grown in different soil sources, ranging from a 20% to 50% increase in aphid performance compared to the “no microbiome” control soil, demonstrating a bottom-up role for soil microbial community. In the second phase, initial soil community, but not previous aphid infestation, impacted aphid performance on plants. Thus, while herbivory altered the rhizosphere microbiome in a soil community-dependent manner, the bottom-up interaction between the microbial community and the plant, not top-down effects of prior herbivore infestation, affected herbivore performance in the following plant generation. These findings suggest that the bottom-up effects of the soil microbial community play an overriding role in herbivore performance in both current and future plant generations and thus are an important target for sustainable control of herbivory in agroecosystems.